Digital disinformation and financial decision-making: understanding the spread of economic conspiracy theories in Indonesia - Sonni, Alem Febri (Frontiers in Human Dynamics, 2025)
This study investigates the proliferation of economic conspiracy theories on Indonesian social media platforms and their impact on financial decision-making, particularly regarding gold investment during the 2025 economic uncertainty period. The research examines how conspiracy narratives spread and influence investment behaviors through a comprehensive mixed-method approach combining network analysis, content analysis, and survey research of 2,847 social media users using stratified random sampling across Indonesian provinces. The findings reveal that 37.4% of surveyed investors reported exposure to economic conspiracy theories, with 22.6% admitting these narratives influenced their investment decisions, with significant variations across demographic groups. Network analysis identified key propagation patterns, showing how conspiracy theories cluster around specific economic events and influencers. The study contributes to the literature on digital misinformation by developing an integrated Digital Disinformation Behavior Model (DDBM) that causally links information cascade theory, social identity theory, and protection motivation theory to explain economic conspiracy theory adoption and subsequent financial behavior. These findings have significant implications for financial literacy programs, regulatory frameworks, and the development of effective counter-disinformation strategies in the digital age.